1965
DOI: 10.1139/b65-105
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Comparisons of Fusarium Populations in Cultivated Fields and Noncultivated Parent Soils

Abstract: In soils of the Salinas watershed Fusarium solani and Fusarium tricinctum were found only in the cultivated soils. Propagules of Fusarium oxysporum were numerous and varied in the cultivated fields but were relatively scarce and existed essentially as a single clone in the noncultivated soils. In the Castroville watershed both F. solani and F. oxysporum were recovered from noncultivated soils fairly frequently.The 'Gibbosum' cultivar of Fusarhim roseum, the most frequently isolated fusarium from field soils, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

1970
1970
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 5 publications
1
27
0
1
Order By: Relevance
“…However, this fungus can cause root and crown rot, in addition to seed, fruit and tuber decay, on a number of plant species, including cereals (Adams et al 1987;Aigbe and Fawole 1999;Chimbekujwo 2000;Demirci and Dane 2003;FedelMoen and Harris 1987;Nash and Snyder 1965;Rai 1979;Reuveni 1982;Strausbaugh et al 2005;Sumbali and Mehrotra 1982). On ginseng, F. equiseti causes seed decay and damping-off on seedlings (Punja 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this fungus can cause root and crown rot, in addition to seed, fruit and tuber decay, on a number of plant species, including cereals (Adams et al 1987;Aigbe and Fawole 1999;Chimbekujwo 2000;Demirci and Dane 2003;FedelMoen and Harris 1987;Nash and Snyder 1965;Rai 1979;Reuveni 1982;Strausbaugh et al 2005;Sumbali and Mehrotra 1982). On ginseng, F. equiseti causes seed decay and damping-off on seedlings (Punja 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The fungus infects the crown and root, and can cause fruit, tuber and seed decay. It has also been isolated from roots of diseased asparagus and wheat plants (Demirci and Dane 2003;Nash and Snyder 1965;Strausbaugh et al 2005;Vujanovic et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, they proposed only a few cultivars that they did not describe and thus left no formal guidelines for future workers. Later, Nash and Snyder (146) and Snyder and Nash (214) named additional cultivars without descriptions. In short, the concept of cultivars was never completely explained or finalized.…”
Section: Gennanyc65mentioning
confidence: 99%
“…several workers have shown that these nonpathogenic strains Fusarium oxysporum is a ubiquitous soil-borne species that may reduce disease incidence and (or) severity of certain can be found in cultivated and noncultivated soils (18,22,30).…”
Section: Introductionmentioning
confidence: 99%